The Effect of CTL Assisted e-LKPD on Increasing Students' Motivation and Learning Outcomes - Rahmi Maulidza; Marini Damanik (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
The purpose of this study was to determine the effect of e-LKPD assisted CTL learning on student motivation and learning outcomes. Samples were taken by purposive sampling as many as 2 classes, namely experimental classes and control classes. The instruments used were multiple choice tests and motivation questionnaires. Data on student learning outcomes and motivation were analyzed by right-side t-test and correlation test. Correlation test to see the relationship between learning motivation and learning outcomes. The results of the cognitive t-test obtained tcount > ttable (3.401> 1.668) which shows Ho is rejected and Ha is accepted, meaning that there is an effect of the CTL learning model assisted by e-LKPD on the learning outcomes of students on acid-base material. The t-test results of learning motivation obtained tcount> ttable (2.191> 1.668) which shows Ho is rejected and Ha is accepted, meaning that there is an effect of CTL learning assisted by e-LKPD on student learning motivation. The correlation results obtained tcount> ttable (0.495> 0.339) indicate that student learning motivation is positively and significantly correlated with student learning outcomes using CTL learning assisted by e-LKPD.